Revisiting Law Enforcement against Revenge Porn Offenders in Cyberspace - Ahmad Ma’mun Fikri (Faculty of Law, Universitas Pekalongan, 2025)
The development of digital technology has increased the threat of cybercrime, including revenge porn, which has a broad impact on victims, psychologically, socially and economically. Although Indonesia already has regulations such as the ITE Law and the Pornography Law, these regulations have not been fully effective in ensnaring perpetrators and providing maximum protection for victims. Meanwhile, other countries such as the United Kingdom and the United States have more specific regulations in dealing with revenge porn. This study aims to analyze the effectiveness of law enforcement against revenge porn in Indonesia and provide recommendations for improving regulations to increase victim protection. The method used is normative legal research with a statutory and comparative approach, which involves analyzing national and international regulations, as well as reviewing court decisions and reports from various institutions. The results show that Indonesian regulations still have gaps in dealing with revenge porn, especially in the aspects of victim protection, content removal mechanisms, and sanctions for perpetrators and digital platforms. Therefore, more progressive legal reforms are needed, including the implementation of the right to be forgotten, increasing sanctions for perpetrators.